Can cattle grazing contribute to butterfly habitat? Using butterfly behavior as an index of habitat quality in an agroecosystem - Bussan, Samantha K.; Schultz, Cheryl B. (Frontiers in Ecology and Evolution, 2023)
The provision of habitat on private agricultural land is vital to the persistence of native species. This study aimed to understand how cattle grazing management strategies influence butterfly behavior. We conducted behavioral experiments with two species of common native butterflies, silvery blue butterflies (Glaucopsyche lygdamus columbia) and ochre ringlet butterflies (Coenonympha california eunomia), at two native prairies with no grazing; two pastures grazed according to “conventional” management; and two pastures grazed according to “conservation” management. We mapped butterfly flight paths to quantify behavioral response to grazing management to test the hypothesis that butterflies have lower diffusion rates in ungrazed and conservation grazed prairies. We used turning angles, length of steps, and flight time to calculate diffusion rates for each individual. We assessed butterfly movement parameters as a function of sex, management type, and their interaction using generalized linear mixed models and used partial least squares regression to assess the effects of resource availability (host plant volume and nectar inflorescence count) on butterfly diffusion rates. We observed the highest silvery blue female step lengths and diffusion rates in conventional grazing and lowest in native prairie. There was moderate evidence that female silvery blue diffusion rates were higher in conservation grazing than native prairie. Neither silvery blue nor ochre ringlet males differed in their movement parameters between management types. Silvery blue diffusion rates were closely associated with their primary host plants (Lupinus spp.). We conclude that there is potential for conservation grazing to contribute to butterfly habitat in the landscape if grazing management practices focus on supporting a diverse plant community with host plants for focal species.